190k views
3 votes
Drag the tiles to the boxes to form correct pairs. Not all tiles will be used.

Match the function with its inverse.


File ATTACHED
THANK YOU

Drag the tiles to the boxes to form correct pairs. Not all tiles will be used. Match-example-1

2 Answers

1 vote

Answer:

Explanation:

Drag the tiles to the boxes to form correct pairs. Not all tiles will be used. Match-example-1
User Zunino
by
4.9k points
4 votes

Answer:

Part 1)
f(x)=(2x-1)/(x+2) ------->
f^(-1)(x)=(-2x-1)/(x-2)

Part 2)
f(x)=(x-1)/(2x+1) ------->
f^(-1)(x)=(-x-1)/(2x-1)

Part 3)
f(x)=(2x+1)/(2x-1) ----->
f^(-1)(x)=(x+1)/(2(x-1))

Part 4)
f(x)=(x+2)/(-2x+1) ---->
f^(-1)(x)=(x-2)/(2x+1)

Part 5)
f(x)=(x+2)/(x-1) ------->
f^(-1)(x)=(x+2)/(x-1)

Explanation:

Part 1) we have


f(x)=(2x-1)/(x+2)

Find the inverse

Let

y=f(x)


y=(2x-1)/(x+2)

Exchange the variables x for y and t for x


x=(2y-1)/(y+2)

Isolate the variable y


x=(2y-1)/(y+2)\\ \\ xy+2x=2y-1\\ \\xy-2y=-2x-1\\ \\y[x-2]=-2x-1\\ \\y=(-2x-1)/(x-2)

Let


f^(-1)(x)=y


f^(-1)(x)=(-2x-1)/(x-2)

Part 2) we have


f(x)=(x-1)/(2x+1)

Find the inverse

Let

y=f(x)


y=(x-1)/(2x+1)

Exchange the variables x for y and t for x


x=(y-1)/(2y+1)

Isolate the variable y


x=(y-1)/(2y+1)\\ \\2xy+x=y-1\\ \\2xy-y=-x-1\\ \\y[2x-1]=-x-1\\ \\y=(-x-1)/(2x-1)

Let


f^(-1)(x)=y


f^(-1)(x)=(-x-1)/(2x-1)

Part 3) we have


f(x)=(2x+1)/(2x-1)

Find the inverse

Let

y=f(x)


y=(2x+1)/(2x-1)

Exchange the variables x for y and t for x


x=(2y+1)/(2y-1)

Isolate the variable y


x=(2y+1)/(2y-1)\\ \\2xy-x=2y+1\\ \\2xy-2y=x+1\\ \\y[2x-2]=x+1\\ \\y=(x+1)/(2(x-1))

Let


f^(-1)(x)=y


f^(-1)(x)=(x+1)/(2(x-1))

Part 4) we have


f(x)=(x+2)/(-2x+1)

Find the inverse

Let

y=f(x)


y=(x+2)/(-2x+1)

Exchange the variables x for y and t for x


x=(y+2)/(-2y+1)

Isolate the variable y


x=(y+2)/(-2y+1)\\ \\-2xy+x=y+2\\ \\-2xy-y=-x+2\\ \\y[-2x-1]=-x+2\\ \\y=(-x+2)/(-2x-1) \\ \\y=(x-2)/(2x+1)

Let


f^(-1)(x)=y


f^(-1)(x)=(x-2)/(2x+1)

Part 5) we have


f(x)=(x+2)/(x-1)

Find the inverse

Let

y=f(x)


y=(x+2)/(x-1)

Exchange the variables x for y and t for x


x=(y+2)/(y-1)

Isolate the variable y


x=(y+2)/(y-1)\\ \\xy-x=y+2\\ \\xy-y=x+2\\ \\y[x-1]=x+2\\ \\y=(x+2)/(x-1)

Let


f^(-1)(x)=y


f^(-1)(x)=(x+2)/(x-1)

User MDMalik
by
4.9k points